Diagnosis and management of primary sclerosing cholangitis-perspectives from a therapeutic endoscopist - Modha, Kunjam (World J Hepatol, 2015)
Primary sclerosing cholangitis (PSC) is a chronic, cholestatic liver condition characterized by inflammation, fibrosis, and destruction of the intra- and extrahepatic bile ducts. The therapeutic endoscopist plays a key role in the diagnosis and management of PSC. In patients presenting with a cholestatic profile, endoscopic retrograde cholangiopancreatography (ERCP) is warranted for a definite diagnosis of PSC. Dominant strictures of the bile duct occur in 36%-57% of PSC patients. Endoscopic balloon dilatation with or without stenting have been employed in the management of dominant strictures. In addition, PSC patients are at increased risk of developing cholangiocarcinoma with a 20% lifetime risk. Brush cytology obtained during ERCP and use of fluorescence in situ hybridization forms the initial diagnostic step in the investigation of patients with dominant biliary strictures. Our review aims to summarize the current evidence supporting the role of a therapeutic endoscopist in the management of PSC patients.